Structural Determinants of Changes in Unemployment in Poland during the COVID-19 Pandemic - Knapińska, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The study analyses the determinants of the level and dynamics of unemployment in Poland in the years 2018–2021. The general hypothesis explored is: the level and structure of unemployment are influenced by the economic situation, the number of job offers reported by employers, migration and border movements, and social attitudes to employment. The article presents an analysis of whether these factors had an impact on the unemployment level in Poland during the COVID-19 pandemic by presenting the development of these measures in the Polish economy.Research Design & Methods: The determinants were presented in the form of quantitative measures available for the quarters of the 2018–2021 period (sometimes the scope and availability of data resulted in a different time range). The data were obtained from public databases of the Central Statistical Office (GUS) and the results of surveys carried out by the Center for Public Opinion Research (CBOS) were used. To achieve the study’s aims, descriptive statistics, analysis, including logical analysis of cause-and-effect influences were used.Findings: The results of the analysis of the presented research material led to conclusions confirming the relationship between the successive waves of disease and the introduction of economic restrictions and the shaping of measures of the economic situation, the number of job offers reported to labour, migration and border traffic offices, as well as social moods regarding employment and opportunities of finding a job. Further research on the causality and determinants of the unemployment situation could lead to the diagnosis of monthly data, or to search for the strength of the tested relationships using more advanced econometric methods.Implications / Recommendations: The analysis included in this paper is an enrichment of the empirical explanation of the economic consequences of the COVID-19 pandemic. This pandemic is an interesting phenomenon not only in the medical sphere, but also carries a number of consequences affecting the world of the economy, which should be investigated with the greatest possible detail.Contribution: This article deepens the understanding the pandemic period and its implication on the labour market and its influence on the unemployment in 2018–2021.